Fever: physiology, pathophysiology, clinical signs and treatment Fieber: Physiologie, Pathophysiologie, klinische Zeichen und Therapie - Marek, I.; Moritz, Katrin; Rascher, Wolfgang; Neubert, Antje (Monatsschrift Kinderheilkunde, 2021)
Background: Fever is a common leading symptom in children presenting in emergency departments and clinical practices. Parents are often uncertain how to treat the febrile child. Objective: This article presents the current knowledge regarding the physiology and pathophysiology of fever in children and the latest evidence on which the recommendations for pharmacotherapy is based. Material and methods: A structured search and analysis of the literature was performed. Results and discussion: Under physiological conditions the temperature regulation center in the hypothalamus controls a stable core body temperature of 37 °C by balancing heat production and loss. Fever develops when mediators of inflammation override the inhibition of excessive heat production mediated by warmth-sensitive neurons in the hypothalamus. Prior to symptomatic treatment of pediatric fever the clinical cause of the fever has to be found and if necessary a causal treatment has to be initiated. This is especially true for high-risk patients, such as neonates, immunosuppressed individuals and children with foreign bodies, such as catheters. In terms of pharmacotherapy two well-established drugs (paracetamol and ibuprofen) are available for the symptomatic treatment of fever. Monotherapy should be preferred over combined or alternating drug administration. Ibuprofen is slightly superior compared to paracetamol with both drugs showing similar safety profiles. There is insufficient evidence to justify the prophylactic use of antipyretics to prevent febrile seizures.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Child; Evidence-based medicine; Febrile seizure; Pharmacotherapy; Thermoregulation